DEVELOPING A NOVEL FRAMEWORK FOR OPTIMIZING COST ESTIMATION IN AFFORDABLE HOUSING PROJECTS USING BUILDING INFORMATION MODELLING (BIM) IN ANAMBRA STATE, NIGERIA (International Journal of Functional Research in Science and Engineering (IJFRSE), 2026)
The reality of affordable housing remained an issue in developing countries such as Nigeria highlights the necessity to find a new solution to the reduction of costs in construction projects. This research establishes the new Building Information Modelling (BIM)-based system that is geared towards reaching cost estimation optimization strength in low cost housing projects in Anambra State in Nigeria. The framework incorporates digital modelling to enhance precision, co-ordination and resource usage by fixing the inaccuracies in conventional techniques of computation of costs which in most cases result in cost overruns, project delays and resource wastage. The study will focus on quantity surveyors, contractors and developers in major city centers like Onitsha, Awka, and Nnewi where there is a severe housing shortage as a result of high urbanization and economic stress. A mixed-method design was used, but primary data using structured questionnaires were collected with 50 quantity surveyors and semi-structured interviews with 20 contractors, and cost data were collected on five ongoing affordable housing projects. It was a demonstration prototype, built in Autodesk Revit and Navisworks that included simplified procedures that are appropriate to a small and medium enterprise (SME) with minimal technological capabilities. Quantitative data were analyzed through SPSS and demonstrated that there were more important difficulties to be overcome as software inaccessibility (mean score 4.2 out of 5 points on the scale), skill gaps (mean 3.8), and thematic analysis of interviews showed such issues as high initial costs and resistance to change. Comparative testing revealed that BIM estimates minimized deviation by 18-25 percent of the traditional techniques, and cost savings of project averages of 12 percent. Participants (n= 354) were mostly male (78), aged 35-50 (mean= 42), had tertiary education (65%), and more than 10 years experience (72%). There were ethical procedures that guaranteed a person the informed consent and confidentiality. The framework provides the scalability of the cost optimization solution that facilitates a sustainable delivery of housing. Policy support such as creation of BIM training, and encouragement of its adoption in the construction industry of Nigeria is suggested. The study plays the role of filling the gap in the quantity surveying literature by harmonizing the digital innovation aspect with the local contexts in order to enable economic advancement by way of effective resource allocation.